Discussion on operation safety and countermeasures of Highway tunnel Traffic Engineering Facilities. Issue 1 (February 2021) - Pang, Rong; Yuan, Yuan; Guo, Xinglong; Zhou, Lijian; Su, Yufeng; Jiang, Mingxing; Li, Xiang
Abstract: In order to further improve the condition of road tunnel traffic engineering facilities, and thus improve the safety of tunnel operations. The paper analyzes the inspection results of traffic engineering facilities in dozens of tunnels in China, and summarizes the common operational safety risks of traffic engineering facilities. Then puts forward corresponding risk prevention and control measures, which is helpful to improve the status of tunnel traffic engineering facilities. It has certain guiding significance for the safety management of road tunnel operation.